Treatment of in vitro-Matured Bovine Oocytes With Tauroursodeoxycholic Acid Modulates the Oxidative Stress Signaling Pathway - Pioltine, Elisa Mariano; Costa, Camila Bortoliero; Barbosa Latorraca, Laís; Franchi, Fernanda Fagali; dos Santos, Priscila Helena; Mingoti, Gisele Zoccal; Paula-Lopes, Fabíola Freitas de; Nogueira, Marcelo Fábio Gouveia (Frontiers in Cell and Developmental Biology, 2021)
In several species, oocyte and embryo competence are improved by the addition of endoplasmic reticulum (ER) stress inhibitors to in vitro maturation (IVM) medium and/or in vitro culture medium. This study aimed to evaluate the effects of three concentrations of tauroursodeoxycholic acid (TUDCA; 50 μM, 200 μM, and 1,000 μM), a chemical chaperone for relieving ER stress, during IVM of bovine cumulus-oocyte complexes for 24 h. Treated oocytes were analyzed for nuclear maturation, reactive oxygen species (ROS) production, mitochondrial activity, and abundance of target transcripts. In addition, the number of pronuclei in oocytes was evaluated after 18-20 h of insemination, and the rates of blastocyst and hatched blastocyst formation were evaluated after 7 and 8/9 days of culture, respectively. We further evaluated the transcript abundance of embryonic quality markers. Our findings showed that supplementation of IVM medium with 200 µM of TUDCA decreased ROS production and increased abundance of transcripts related to antioxidant activity in oocytes (CAT, GPX1, and HMOX1) and embryos (GPX1 and PRDX3). Interestingly, high concentration of TUDCA (1,000 µM) was toxic to oocytes, reducing the nuclear maturation rate, decreasing mitochondrial activity, and increasing the abundance of ER stress (HSPA5) and cellular apoptosis (CASP3 and CD40) related transcripts. The results of this study suggest that treatment with 200 µM of TUDCA is associated with a greater resistance to oxidative stress and, indirectly with ER stress relief in bovine oocytes.